Irreverently sensual: Trento by Leónidas Lamborghini (Anclajes, 2011)
The writing of Leónidas Lamborghini is characterized by a critical reading of the Occidental literary tradition. Unlike other forms of more orthodox intertextual relations, the entailments tried by the author transgress the conventions and carry far the intertextual strategies composing complicated mosaics, plagued of references to previous texts. This article analyze one of its last books, Trento (2003), where is deconstructed the council of Trento, during which the body of the church would decide the dogmatic aspects more substitutes of the Catholicism. Especially, it interests to us to analyze the form in that the text subverts values, judges postulates, deceives of the fanaticisms, it enthrones the sexuality and, really, reveals the contradictions of the institution Church, from a carnival perspective that parody facilitates. It is that opposition, which the laughter and the “moral of buffoon” prop up, the one that prints in the volume his more evident condition of revolutionary and satirical re-writing of History.
Keywords: argentine poetry; Leónidas Lamborghini; intertextuality; parody